The Abda’u Ritual: Ethnographic Communication Study of Tulehu Society in the Moluccas, Indonesia - Ridwan, M.; Toisuta, Hasbollah; Sulaeman, Sulaeman; Salam, Nur (International Journal of Criminology and Sociology, 2022)
The study focuses on the emerging phenomenon of abda’u ritual at the Eid al-Adha celebration in the month of Dhu al-Hijjah. Eid al-Adha celebration by the Tulehu society in the Moluccas, Indonesia is to identify the trust and values local tradition as a form of struggle, defense and flag upholding, struggle for sacrificial animals with ideology upholding of Islamic teachings. This ritual uses the communication media of three goats to be sacrificial animals and is distributed to three the indigenous village which is contested by abda’u participants. This research employed a subjective interpretive paradigm with an ethnographic communication approach pioneered by Dell Hymes based on a symbolic interaction perspective the abda’u ritual at the Eid al-Adha celebration. The symbol of devotion to Allah is a distribution by sharing with other communities that become the glue to arouse sacrifice through the sentence Lailaha ilallah muhammadarrasulullah. The findings show that the abda’u communication ritual is formed based on awareness to preserve the procession of the sacrifice of the sacrificed animals, and the social solidarity, syiar of Islam, enforcing Islam ideological through devotion to Allah.